An electron paramagnetic resonance study of carbon based electronic materials - Collins, Michael Peter (Trinity College (Dublin, Ireland). School of Physics, 2000)
Electron paramagnetic resonance (EPR) measurements have been made on films of hydrogenated amorphous carbon (a-C: H) and ion implanted 6H-SiC. We examine several sets of a-C: H films. The first and second sets of films were grown by plasma-enhanced chemical vapour deposition (PECVD) on the ground electrode, which produces polymeric a-C: H, the thickness is varied in the first set of a-C: H films while the nitrogen content is varied in the second. The third set of a-C: H films was grown, on the live electrode and deposited with a range of negative self-bias voltages (Vb), from 50 to 540V. This produced films with structures ranging from diamond like a-C: H (DLC) to graphite-like a-C: H (GLHC). A fourth set of a-C: H films was produced by magnetically confined PECVD, these films initially had a DLC structure (without nitrogen) and were produced with various nitrogen contents. In the first (polymeric a-C:H) set we find two defects are present, one due to defects from the Si substrate and possibly at the C/Si interface the second defect due to carbon dangling bonds, uniformly distributed through the bulk of the film.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin